2018
DOI: 10.1016/j.devcel.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitotic Cell-Substrate Adhesion Re-modeling in Animal Cell Division

Abstract: Animal cells undergo a dramatic series of shape changes as they divide, which depend on re-modeling of cell-substrate adhesions. Here, we show that while focal adhesion complexes are disassembled during mitotic rounding, integrins remain in place. These integrin-rich contacts connect mitotic cells to the underlying substrate throughout mitosis, guide polarized cell migration following mitotic exit, and are functionally important, since adherent cells undergo division failure when removed from the substrate. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(146 citation statements)
references
References 71 publications
10
135
1
Order By: Relevance
“…While almost all proliferating animal cells undergo a degree of mitotic rounding, different cell types exhibit striking differences in the extent to which they round 1,12 . In this context, we previously noted that cancer cell lines tend to round up more than many non-transformed cells 2 . There are two likely explanations for this.…”
Section: Introductionmentioning
confidence: 97%
“…While almost all proliferating animal cells undergo a degree of mitotic rounding, different cell types exhibit striking differences in the extent to which they round 1,12 . In this context, we previously noted that cancer cell lines tend to round up more than many non-transformed cells 2 . There are two likely explanations for this.…”
Section: Introductionmentioning
confidence: 97%
“…This likely frees up a pool of actin monomers (Kaur et al, 2014), which is then used to assemble a thin (Clark et al, 2013), mechanically rigid (Fischer-Friedrich et al, 2015), cortical actomyosin network that drives mitotic rounding (Reinsch & Karsenti, 1994;Ragkousi & Gibson, 2014;Sorce et al, 2015). While the mechanisms underlying this mitotic switch in actin organisation are not well understood, the process likely involves the following: (i) the loss of interphase focal adhesions (Dix et al, 2018;Lock et al, 2018), (ii) the loss of Arp2/3-dependent lamellipodia (Ibarra et al, 2005;Bovellan et al, 2014;Rosa et al, 2015) and (iii) the activation of formins downstream of Ect2/Pbl and the GTPase Rho (Maddox & Burridge, 2003;Matthews et al, 2012;Rosa et al, 2015;Chugh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the de-phosphorylation of ERM proteins, which crosslink actin to the plasma membrane (Rodrigues et al, 2015), to the loss of anillin (Kiyomitsu & Cheeseman, 2013) and to activation of SCAR/WAVE and the Arp2/3 complex at opposing cell poles (Zhang & Robinson, 2005;King et al, 2010;Nezis et al, 2010;Bastos et al, 2012;Luo et al, 2014). In some instances, the process of polar relaxation and cell re-spreading is sufficient to drive division in cells that lack an actomyosin ring (Neujahr et al, 1997;Dix et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In ~70% of the cps1-191 spheroplasts (37 out of 53 spheroplasts) that underwent cytofission, the rings contracted till mid-phase of division and disassembled before division into two entities. We Previous studies suggested under certain circumstances, some eukaryotic cells are able to divide without an actomyosin ring (Flor-Parra et al, 2014;Proctor et al, 2012;Dix et al, 2018;Choudhary et al, 2013). To see if the cytofission was driven by contraction of the actomyosin ring, we first perturbed the functions of rings using Latrunculin-A (Lat-A) to inhibit actin polymerization (Fujiwara et al, 2018;Morton et al, 2000).…”
Section: Resultsmentioning
confidence: 98%